Negative electrode for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery including the same
The introduction of a silicon-based active material and a skeletal-forming agent with a siloxane bond in the negative electrode of nonaqueous electrolyte secondary batteries addresses the issue of void formation, enhancing energy density and cycle durability while maintaining structural integrity.
Patent Information
- Application Number
- JP2021014106
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-01
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2041-02-01
AI Technical Summary
Conventional nonaqueous electrolyte secondary batteries face limitations in energy density and cycle durability due to the inability to effectively suppress the generation of voids within porous metal bodies used in negative electrodes, leading to structural deterioration and reduced manufacturing accuracy.
A negative electrode design featuring a current collector made of a porous metal body, with a silicon-based first negative electrode active material disposed on the inner surface of the pores, a skeletal-forming agent containing a silicate with a siloxane bond, and a second negative electrode active material, which helps to prevent void formation and enhance structural integrity.
This design effectively suppresses the generation of voids within the porous metal body, thereby improving energy density and cycle durability while maintaining the structural integrity of the electrode, even under conditions of high expansion and contraction.
Smart Images

Figure 0007657060000002 
Figure 0007657060000003 
Figure 0007657060000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode for a non-aqueous electrolyte secondary battery and a non-aqueous electrolyte secondary battery including the same. [Background technology]
[0002] In recent years, non-aqueous electrolyte secondary batteries such as lithium ion secondary batteries are increasingly being used in automobiles and the like because they are small, lightweight, and provide high output. A non-aqueous electrolyte secondary battery is a general term for a battery system that uses an electrolyte that does not contain water as a main component, and is a chargeable and dischargeable power storage device. For example, lithium ion batteries, lithium polymer batteries, lithium solid-state batteries, lithium air batteries, lithium sulfur batteries, sodium ion batteries, potassium ion batteries, multivalent ion batteries, fluoride batteries, sodium sulfur batteries, and the like are known. This non-aqueous electrolyte secondary battery is mainly composed of a positive electrode, a negative electrode, and an electrolyte. In addition, when the electrolyte has fluidity, a separator is further interposed between the positive electrode and the negative electrode.
[0003] For example, a technique has been disclosed in which a skeletal former containing a silicate having a siloxane bond is present at least on the surface of an active material, and the skeletal former is allowed to penetrate from the surface to the inside, in order to improve the battery life (see, for example, Patent Document 1). This technique is said to be able to form a strong skeleton in the active material, thereby improving the battery life. Also disclosed is a technique in which the skeletal former is applied to a negative electrode containing a silicon (Si)-based active material (see, for example, Patent Document 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 6369818 [Patent Document 2] Patent No. 6149147 Summary of the Invention [Problem to be solved by the invention]
[0005] Meanwhile, there is a demand for improving the energy density of the non-aqueous electrolyte secondary battery. In order to improve the energy density, it is considered effective to increase the thickness of the negative electrode and to increase the density of the amount of negative electrode active material. However, in the conventional technology, there is a limit to the thickness of the negative electrode in terms of the production of the negative electrode. Specifically, the practical thickness of the film that can be applied to the conventional current collector foil for the mixture layer is less than 100 μm. If the film thickness is 100 μm or more, problems such as uneven coating, cracks, and peeling occur, making it difficult to produce a highly accurate negative electrode.
[0006] In addition, due to the balance between the binding strength of the binder and the expansion and contraction of the negative electrode active material, there is a limit to the amount of negative electrode active material per unit area from the viewpoint of durability. Specifically, the negative electrode active material capacity per unit area is 4 mAh / cm 2 The limit is about 50 μm (film thickness), and sufficient cycle performance cannot be maintained beyond that. On the other hand, the active material capacity is 4 mAh / cm 2 If the thickness is less than this, no improvement in energy density can be expected.
[0007] In order to solve the above problems, it is conceivable to apply a porous metal body to the current collector of the negative electrode of a non-aqueous electrolyte secondary battery and fill the porous metal body with an electrode mixture. In a non-aqueous electrolyte secondary battery, when a current collector made of a porous metal body, an electrode active material made of a silicon-based material as a negative electrode active material, and a skeleton-forming agent that coats the current collector and the electrode active material are applied to the negative electrode, it has been found that if the skeleton-forming agent does not penetrate into the inside of the negative electrode sufficiently, voids are generated inside the porous metal body. It has also been found that a non-aqueous electrolyte secondary battery using such a negative electrode causes structural deterioration inside the electrode due to repeated charging and discharging, which deteriorates the battery performance.
[0008] Therefore, there is a need for a negative electrode for a nonaqueous electrolyte secondary battery that can suppress the occurrence of voids inside a porous metal body, thereby suppressing deterioration in durability and deterioration of the electrode structure, and improving energy density and cycle durability, as well as a nonaqueous electrolyte secondary battery including the same.
[0009] The present invention has been made in view of the above, and has an object to provide a negative electrode for a nonaqueous electrolyte secondary battery that can suppress the occurrence of voids inside a porous metal body, thereby suppressing deterioration in durability and deterioration of the electrode structure, and improving energy density and cycle durability, and a nonaqueous electrolyte secondary battery including the same. [Means for solving the problem]
[0010] (1) In order to achieve the above object, the present invention provides a negative electrode for a non-aqueous electrolyte secondary battery, comprising: a current collector formed of a porous metal body; and a negative electrode material disposed in pores of the porous metal body, the negative electrode material being disposed on inner surfaces of the pores and comprising: a first negative electrode active material formed of a silicon-based material; a skeleton-forming agent disposed on the first negative electrode active material and including a silicate having a siloxane bond; and a second negative electrode active material disposed on the skeleton-forming agent.
[0011] (2) In the negative electrode for a non-aqueous electrolyte secondary battery of (1), the negative electrode material may further include a conductive assistant disposed between the framework forming agent and the second negative electrode active material.
[0012] (3) In the negative electrode for a non-aqueous electrolyte secondary battery according to (1) or (2), the framework forming agent may contain a silicate represented by the following general formula (1): [C1] A2O·nSiO2···Formula (1) [In the above general formula (1), A represents an alkali metal.]
[0013] (4) In the negative electrode for a nonaqueous electrolyte secondary battery according to any one of (1) to (3), the porous metal body may be a foamed metal body.
[0014] (5) The present invention also provides a nonaqueous electrolyte secondary battery comprising a negative electrode for a nonaqueous electrolyte secondary battery according to any one of (1) to (4). Effect of the Invention
[0015] According to the present invention, it is possible to provide a negative electrode for a nonaqueous electrolyte secondary battery, which can suppress the occurrence of voids inside a porous metal body, thereby suppressing durability deterioration and improving energy density, and a nonaqueous electrolyte secondary battery including the same. [Brief description of the drawings]
[0016] [Figure 1] 1 is a diagram illustrating a schematic configuration of a negative electrode for a nonaqueous electrolyte secondary battery according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is a diagram illustrating a configuration of a negative electrode for a nonaqueous electrolyte secondary battery according to the first embodiment of the present invention, further including a conductive assistant and a binder. [Diagram 3] FIG. 2 is a graph showing the relationship between the number of cycles and the capacity (mAh / g) of an active material in Examples 1 to 4 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Hereinafter, a first embodiment of the present invention will be described in detail with reference to the drawings.
[0018] [Negative electrode] 1 is a diagram showing a schematic configuration of a negative electrode 1 for a non-aqueous electrolyte secondary battery according to the present embodiment. The negative electrode 1 for a non-aqueous electrolyte secondary battery according to the present embodiment includes a current collector 11 made of a porous metal body, and a negative electrode material 12 disposed in the pores of the porous metal body. The negative electrode material 12 also includes a first negative electrode active material 13 disposed on the inner surface of the pores and made of a silicon-based material, a framework forming agent 14 disposed on the first negative electrode active material 13 and containing a silicate having a siloxane bond, and a second negative electrode active material 17 disposed on the framework forming agent. For example, by applying this embodiment to a negative electrode for a lithium ion secondary battery, it is possible to provide a negative electrode for a lithium ion secondary battery that can suppress the increase or decrease in the voids inside the porous metal body, thereby suppressing the deterioration of durability and the deterioration of the structure of the electrode, and can improve the energy density and cycle durability, and a lithium ion secondary battery including the same. Below, an example in which this embodiment is applied to a negative electrode for a lithium ion secondary battery will be described in detail, but various additions, modifications, or deletions are possible within the scope of the present invention.
[0019] The current collector 11 is made of a porous metal body. Examples of the current collector 11 include mesh, woven fabric, nonwoven fabric, embossed body, punched body, expanded body, and foamed body, and a metal foam is preferably used. Among them, a metal foam having a three-dimensional mesh structure with continuous pores is preferably used, and for example, Celmet (registered trademark) (manufactured by Sumitomo Electric Industries, Ltd.) can be used.
[0020] The material of the porous metal body is not particularly limited as long as it has electronic conductivity and can pass electricity through the held electrode material. For example, conductive metals such as Al, Al alloys, Ni, Ni-Cr alloys, Fe, Cu, Ti, Cr, Au, Mo, W, Ta, Pt, Ru, and Rh, and conductive alloys containing two or more of these conductive metals (stainless steels (SUS304, SUS316, SUS316L, YUS270, etc.) can be used. When a conductive metal or conductive alloy other than the above is used, it may have a multilayer structure of different metals, for example, Fe coated with Cu or Ni. Among them, Ni or a Ni alloy is preferably used because of its excellent electronic conductivity and reduction resistance.
[0021] The thickness of the porous metal body is preferably 10 μm or more, more preferably 50 μm or more, and is preferably 1 mm or less, more preferably 800 μm or less.
[0022] The average pore size of the porous metal body is preferably 800 μm or less. When the average pore size of the porous metal body is within this range, the distance between the first negative electrode active material 13 filled or supported inside the porous metal body and the metal skeleton is stable, the electronic conductivity is improved, and an increase in the internal resistance of the battery is suppressed. In addition, even if a volume change occurs due to charging and discharging, the electrode mixture can be prevented from falling off.
[0023] The specific surface area of the porous metal body is preferably 1000 to 10000 m 2 / m 3 This is 2 to 10 times the specific surface area of a conventional current collector foil. When the specific surface area of the porous metal body is within this range, the contact between the electrode mixture and the current collector 11 is improved, and an increase in the internal resistance of the battery is suppressed. A more preferable specific surface area is 4000 to 7000 m. 2 / m 3 It is.
[0024] The porosity of the porous metal body is preferably 90 to 99%. When the porosity of the porous metal body is within this range, it is possible to increase the amount of electrode mixture to be filled, and the energy density of the battery is improved. Specifically, when the porosity exceeds 99%, the mechanical strength of the porous metal body is significantly reduced, and the porous metal body is easily damaged by the volume change of the electrode accompanying charging and discharging. Conversely, when the porosity is less than 90%, not only the amount of electrode mixture to be filled is reduced, but also the ionic conductivity of the electrode is reduced, making it difficult to obtain sufficient input / output characteristics. From these viewpoints, a more preferable porosity is 93 to 98%.
[0025] The electrode weight of the porous metal body is preferably 1 to 100 mg / cm 2 When the electrode area density of the porous metal body is within this range, the active material capacity can be fully expressed, and the electrode can exhibit the capacity as designed. A more preferable electrode area density is 5 to 60 mg / cm. 2 It is.
[0026] As the first negative electrode active material 13, a material capable of reversibly absorbing and releasing lithium ions is used, and specifically, a negative electrode active material composed of a high-capacity silicon-based material is used. Examples of silicon-based materials include silicon alone, silicon alloys, silicon oxides, silicon compounds, and the like. Here, silicon alone refers to crystalline or amorphous silicon with a purity of 95% by mass or more. The silicon alloy refers to a Si-M alloy consisting of silicon and another transition element M, where M is, for example, Al, Mg, La, Ag, Sn, Ti, Y, Cr, Ni, Zr, V, Nb, Mo, and the like, and may be a complete solid solution type alloy, a eutectic alloy, a hypoeutectic alloy, a hypereutectic alloy, or a peritectic type alloy. The silicon oxide refers to an oxide of silicon or a complex consisting of silicon alone and SiO2, and the element ratio of Si to O may be 1:1.7 or less. The silicon compound is a substance in which silicon and two or more other elements are chemically bonded. Among these, silicon alone is preferable because it can form an interface layer described later well. Alternatively, a mixture or composite of a silicon-based material and a carbon-based material may be used.
[0027] In the present invention, the first negative electrode active material 13 is preferably disposed on the inner surfaces of the pores of the porous metal body.
[0028] The shape of the silicon-based material is not particularly limited, and may be a spherical, elliptical, faceted, strip-like, fibrous, flake-like, doughnut-like, or hollow powder, and these may be single particles or granules.
[0029] The negative electrode active material 13 made of a silicon-based material has an expansion rate of 10% or more due to charging and discharging. That is, the negative electrode active material 13 expands and contracts significantly during charging and discharging, but by using the framework forming agent 14 described later, it is possible to suppress deterioration in durability due to such expansion and contraction.
[0030] From the viewpoint of obtaining excellent cycle characteristics of the electrode and high input / output characteristics, the particle size of the silicon-based material is preferably 1.0 μm to 15 μm.
[0031] From the viewpoint of ensuring electrical conductivity when the active material expands and contracts during charging and discharging, the amount (area weight) of the first negative electrode active material 13 supported in the porous metal body is 1.0 to 12 mg / cm 2 A more preferable supported amount (area weight) of the first negative electrode active material 13 is 2.0 to 8.0 mg / cm 2 It is.
[0032] Furthermore, the first negative electrode active material 13 may be configured to contain, in addition to the above-mentioned silicon-based material, a carbon-based material (graphite, hard carbon, soft carbon, etc.) and / or a conductive assistant 15. When the first negative electrode active material 13 is configured to contain a carbon-based material and / or a conductive assistant 15, from the viewpoint of improving the output of the battery, the content of the conductive assistant 15 is preferably 1 to 10 mass % when the total of the first negative electrode active material 13, the carbon-based material, and the conductive assistant 15 is taken as 100 mass %. The content of the conductive assistant 15 is more preferably 2 to 7 mass %.
[0033] A skeleton-forming agent 14 containing a silicate having a siloxane bond is used as the skeleton-forming agent 14. More specifically, the skeleton-forming agent 14 preferably contains a silicate represented by the following general formula (1). [Case 2] A2O·nSiO2···Formula (1)
[0034] In the above general formula (1), A represents an alkali metal. Among them, A is preferably at least one of lithium (Li), sodium (Na) and potassium (K). By using such an alkali metal salt of silicic acid having a siloxane bond as a framework forming agent, a lithium ion secondary battery having high strength, excellent heat resistance and excellent cycle life can be obtained.
[0035] In the above general formula (1), n is preferably 1.6 or more and 3.9 or less. When n is within this range, an appropriate viscosity is obtained when the skeletal forming agent 14 is mixed with water to form a skeletal forming agent liquid, and as described below, when the skeletal forming agent 14 is applied to a negative electrode containing silicon as the negative electrode active material 13, the skeletal forming agent 14 is easily permeated into the negative electrode material 12. Therefore, a lithium ion secondary battery with high strength, excellent heat resistance, and excellent cycle life can be more reliably obtained. More preferably, n is 2.0 or more and 3.5 or less.
[0036] The silicate is preferably amorphous. Since an amorphous silicate has a disordered molecular arrangement, it does not break in a specific direction like a crystal. Therefore, by using an amorphous silicate as the framework forming agent 14, the cycle life characteristics are improved.
[0037] For example, by applying the above-mentioned skeletal forming agent liquid to a negative electrode containing silicon as the first negative electrode active material 13 , the skeletal forming agent 14 permeates between the first negative electrode active material 13 . It is presumed that silicon constituting the negative electrode active material 13 and the silicate constituting the skeleton-forming agent 14 are fused together, and that, for example, hydrolyzed silicate undergoes a dehydration reaction (condensation reaction of silanol groups) by heating to form a siloxane bond (-Si-O-Si-). That is, in the negative electrode 1 for a lithium ion secondary battery of this embodiment, an interface layer made of an inorganic substance is formed at the interface between the first negative electrode active material 13 and the skeleton-forming agent 14, and this interface layer contains silicon derived from the siloxane bond and an alkali metal generated by hydrolysis of the silicate or the like. The presence of this interface layer firmly bonds the first negative electrode active material 13 and the skeleton-forming agent 14, and as a result, the first negative electrode active material 13 can be fixed or supported inside the porous metal body by the metal skeleton of the current collector 11 made of a porous metal body and the skeleton-forming agent 14, and therefore it is presumed that excellent cycle life characteristics are obtained. In the present invention, the skeleton forming agent 14 is preferably disposed on the first negative electrode active material 13. This is because the first negative electrode active material 13 can be fixed or supported inside the pores of the porous metal body by the metal skeleton of the current collector 11 made of a porous metal body and the skeleton forming agent 14.
[0038] In this embodiment, the ratio of alkali metal atoms to all constituent atoms of the interface layer is preferably higher than the ratio of alkali metal atoms to all constituent atoms of the skeleton forming agent 14. More specifically, the ratio of alkali metal atoms to all constituent atoms of the interface layer is preferably 5 times or more the ratio of alkali metal atoms to all constituent atoms of the skeleton forming agent 14. This makes the bond between the first negative electrode active material 13 and the skeleton forming agent 14 stronger, and peeling due to expansion and contraction of the first negative electrode active material 13 during charging and discharging and the occurrence of wrinkles and cracks in the current collector 11 are further suppressed, thereby improving the cycle life.
[0039] The thickness of the interface layer is preferably 3 to 30 nm. When the thickness of the interface layer is within this range, the bond between the first negative electrode active material 13 and the framework forming agent 14 becomes stronger, peeling due to expansion and contraction of the first negative electrode active material 13 during charging and discharging and the occurrence of wrinkles and cracks in the current collector 11 are further suppressed, and the cycle life is further improved.
[0040] The skeleton forming agent 14 of the present embodiment may contain a surfactant. This improves the lyophilicity of the skeleton forming agent 14 into the negative electrode material 12, and the skeleton forming agent 14 uniformly penetrates into the negative electrode material 12. Therefore, a uniform skeleton is formed between the first negative electrode active materials 13 in the negative electrode material 12, and the cycle life characteristics are further improved.
[0041] The content (density) of the framework forming agent 14 relative to the negative electrode material 12 is 0.5 to 2.0 mg / cm 2 If the content of the framework forming agent 14 relative to the negative electrode material 12 is within this range, the above-mentioned effects of using the framework forming agent 14 are more reliably exhibited.
[0042] When the total solid content of the first negative electrode active material 13, the skeletal former 14, and the second negative electrode active material 17 is taken as 100% by mass, the content of the skeletal former 14 is preferably 3.0 to 40.0% by mass. When the content of the skeletal former 14 is within this range, the above-mentioned effect of using the skeletal former 14 is more reliably exhibited. By making the content of the skeletal former 14 in the negative electrode material 12 3.0% by mass or more, the function of the skeletal former 14 can be more fully obtained. In addition, by making the content of the skeletal former 14 40.0% by mass or less, the decrease in energy density can be more effectively prevented. The content of the skeletal former 14 is more preferably 5.0 to 30.0% by mass.
[0043] Here, in the negative electrode 1 for a nonaqueous electrolyte secondary battery of this embodiment, the skeletal former 14 is disposed at least at the interface between the negative electrode material 12 and the current collector 11. More specifically, the skeletal former 14 is disposed not only at the interface between the current collector 11 and the negative electrode material 12 but also uniformly throughout the negative electrode material 12, and is present in a dispersed state between the first negative electrode active materials 13. In contrast, in a conventional negative electrode for a nonaqueous electrolyte secondary battery, the skeletal former is unevenly distributed on the surface of the negative electrode material.
[0044] The lithium ion secondary battery negative electrode 1 according to this embodiment also includes a second negative electrode active material 17. As the second negative electrode active material, a negative electrode active material that does not expand or contract during charging and discharging or that has a property of expanding and contracting only slightly is preferably used. By including the second negative electrode active material 17 inside the pores of the current collector 11 made of a porous metal body, it is possible to fill voids that occur in the pores when the permeation of the framework forming agent 14 into the current collector 11 is insufficient, and it is presumed that this can suppress the falling off of the negative electrode material 12 that occurs during the expansion and contraction of the first negative electrode active material 13. In the present invention, the second negative electrode active material is preferably disposed on the skeletal forming agent. This is because the second negative electrode active material can be disposed in the gaps generated by disposing the first negative electrode active material 13 and the skeletal forming agent 14 in the described order inside the pores of the porous metal body. Note that, unlike the first negative electrode active material, the second negative electrode active material does not necessarily need to be bonded or fixed to the skeletal forming agent. Specific examples of materials preferably used as the second negative electrode active material include silicon monoxide (SiO), silicon carbide (SiC), tin (Sn), graphite, carbon-based materials (graphite (Gr), hard carbon, soft carbon, etc.), lithium titanate (LTO), etc., and one or more of these can be used. From the viewpoint of improving the energy density, silicon monoxide is preferred.
[0045] The weight of the second negative electrode active material is 1 to 40 mg / cm from the viewpoint of energy density. 2 The more preferable weight of the second negative electrode active material is 5 to 15 mg / cm. 2 The total weight of the first negative electrode active material and the second negative electrode active material is 10 to 50 mg / cm from the viewpoint of suppressing deterioration due to durability and improving the energy density. 2 The total weight of the first negative electrode active material and the second negative electrode active material is more preferably 10 to 20 mg / cm. 2 It is. From the viewpoints of energy density and durability, the mixing ratio of the first negative electrode active material to the second negative electrode active material is preferably 1:2 to 1:5 by weight, and more preferably 1:2 to 1:3 by weight.
[0046] The thickness of the negative electrode 1 for a nonaqueous electrolyte secondary battery of this embodiment having the above configuration is preferably 50 μm to 1000 μm. If the thickness of the negative electrode 1 for a nonaqueous electrolyte secondary battery is within this range, durability deterioration can be suppressed and energy density can be improved compared to conventional negative electrodes. The thickness of the negative electrode 1 for a nonaqueous electrolyte secondary battery is more preferably 150 μm to 800 μm.
[0047] In the negative electrode 1 for a nonaqueous electrolyte secondary battery of this embodiment, the distance between the current collector 11 made of a porous metal body and the first negative electrode active material 13 is preferably 50 μm or less. If the distance between the current collector 11 made of a porous metal body and the first negative electrode active material 13 is 50 μm or less, durability deterioration can be suppressed. More preferably, the distance between the current collector 11 made of a porous metal body and the first negative electrode active material 13 is 30 μm or less.
[0048] The negative electrode 1 for lithium ion secondary batteries according to the present embodiment may include a conductive assistant 15. The conductive assistant 15 is not particularly limited as long as it has electronic conductivity, and metals, carbon materials, conductive polymers, conductive glass, and the like can be used. Specific examples include acetylene black (AB), ketjen black (KB), furnace black (FB), thermal black, lamp black, channel black, roller black, disc black, carbon black (CB), carbon fiber (e.g., vapor-grown carbon fiber VGCF (registered trademark)), carbon nanotubes (CNT), carbon nanohorns, graphite, graphene, glassy carbon, amorphous carbon, and the like, and one or more of these can be used. In the present embodiment, when a conductive assistant is included, the conductivity in the electrode can be improved and the internal resistance can be reduced by using a carbon black-based carbon material, a furnace-based carbon material, or a fibrous carbon material as the conductive assistant 15. In addition, by using a graphene-based carbon material as the conductive assistant 15, the structural deterioration of the electrode due to repeated charging and discharging can be suppressed, and cycle durability can be improved.
[0049] In the present embodiment, when the conductive assistant 15 and / or the binder 16 are contained, the content of the conductive assistant 15 is preferably 0 to 20.0 mass % when the total of the first negative electrode active material 13, the conductive assistant 15, the binder 16, and the second negative electrode active material 17 is taken as 100 mass %. If the content of the conductive assistant 15 is within this range, the conductivity can be improved without decreasing the negative electrode capacity density, and voids capable of retaining a sufficient amount of the skeleton forming agent 14 can be formed inside the negative electrode material 12. The content of the conductive assistant 15 is more preferably 2 to 10 mass %.
[0050] In the present embodiment, when the conductive assistant 15 is contained, the conductive assistant 15 has a bulk density of 0.04 to 0.25 mg / cm 3When the bulk density of the conductive assistant 15 is within this range, the above-mentioned skeletal forming agent 14 can be sufficiently impregnated, and the above-mentioned effect of the skeletal forming agent 14 can be fully exhibited. A more preferable bulk density of the conductive assistant 15 is 0.04 to 0.15 mg / cm. 3 It is.
[0051] In the present invention, when the conductive assistant 15 is contained in the negative electrode 1 for a non-aqueous electrolyte secondary battery, it is preferable to dispose it between the framework forming agent and the second negative electrode active material 17 . When the negative electrode 1 for a non-aqueous electrolyte secondary battery of this embodiment contains a conductive assistant 15, the conductive assistant is disposed at least at the interface between the current collector 11 and the negative electrode material 12, specifically, on the surfaces of the current collector 11, the first negative electrode active material 13, and the framework forming agent 14, and in gaps formed by the arrangement of these. More specifically, the conductive assistant 15 is disposed not only at the interface between the current collector 11 and the negative electrode material 12, but also throughout the negative electrode material 12, and is dispersed and present in gaps formed between the first negative electrode active materials 13, the current collector 11, the first negative electrode active material 13, and the framework forming agent 14. In contrast, when a conventional negative electrode for a non-aqueous electrolyte secondary battery contains a conductive assistant, the conductive assistant is unevenly distributed on the surface of the negative electrode material.
[0052] The negative electrode 1 for a lithium ion secondary battery according to the present embodiment may contain a binder 16. Examples of the binder 16 include polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), polyimide (PI), polyamide, polyamideimide, aramid, polyacrylic, styrene butadiene rubber (SBR), ethylene-vinyl acetate copolymer (EVA), styrene-ethylene-butylene-styrene copolymer (SEBS), carboxymethyl cellulose (CMC), xanthan gum, polyvinyl alcohol (PVA), ethylene vinyl alcohol, polyvinyl butyral (PVB), ethylene vinyl alcohol, polyethylene (PE), polypropylene (PP), polyacrylic acid, lithium polyacrylate, sodium polyacrylate, potassium polyacrylate, ammonium polyacrylate, methyl polyacrylate, ethyl polyacrylate, amine polyacrylate, ethylene polyacrylate, and the like. Organic materials such as ester, epoxy resin, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), nylon, vinyl chloride, silicone rubber, nitrile rubber, cyanoacrylate, urea resin, melamine resin, phenolic resin, latex, polyurethane, silylated urethane, nitrocellulose, dextrin, polyvinylpyrrolidone, vinyl acetate, polystyrene, chloropropylene, resorcinol resin, polyaromatic, modified silicone, methacrylic resin, polybutene, butyl rubber, 2-propenoic acid, cyanoacrylic acid, methyl methacrylate, glycidyl methacrylate, acrylic oligomer, 2-hydroxyethyl acrylate, alginic acid, starch, lacquer, sucrose, glue, casein, and cellulose nanofibers may be used alone or in combination of two or more.
[0053] In addition, a mixture of the above-mentioned various organic binders and inorganic binders may be used. Examples of inorganic binders include silicate-based, phosphate-based, sol-based, and cement-based binders. For example, lithium silicate, sodium silicate, potassium silicate, cesium silicate, guanidine silicate, ammonium silicate, silicofluoride, borate, lithium aluminate, sodium aluminate, potassium aluminate, aluminosilicate, lithium aluminate, sodium aluminate, potassium aluminate, polyaluminum chloride, polyaluminum sulfate, polyaluminum silicate sulfate, aluminum sulfate, aluminum nitrate, ammonium alum, lithium alum, sodium alum, potassium alum, chrome alum, iron alum, manganese alum, nickel ammonium sulfate, diatomaceous earth, polyzirconoxane, polytanthane taloxane, mullite, white carbon, silica sol, colloidal silica, fumed silica, alumina sol, colloidal alumina, fumed alumina, zirconium sol, silicic acid ... Inorganic materials such as conia sol, colloidal zirconia, fumed zirconia, magnesia sol, colloidal magnesia, fumed magnesia, calcia sol, colloidal calcia, fumed calcia, titania sol, colloidal titania, fumed titania, zeolite, silicoaluminophosphate zeolite, sepiolite, montmorillonite, kaolin, saponite, aluminum phosphate, magnesium phosphate, calcium phosphate, iron phosphate, copper phosphate, zinc phosphate, titanium phosphate, manganese phosphate, barium phosphate, tin phosphate, low melting point glass, plaster, gypsum, magnesium cement, litharge cement, Portland cement, blast furnace cement, fly ash cement, silica cement, phosphate cement, concrete, and solid electrolytes may be used alone or in combination of two or more.
[0054] In addition, when the present embodiment includes the binder 16, the first negative electrode active material 13 and the skeleton forming agent 14 are firmly bonded by the above-mentioned interface layer formed by using the skeleton forming agent 14, so all of the above-mentioned binders 16 can be used. When the present embodiment includes the conductive assistant 15 and / or the binder 16, the content of the binder 16 is preferably 0.1 to 60 mass% when the total of the first negative electrode active material 13, the conductive assistant 15, the binder 16, and the second negative electrode active material 17 is taken as 100 mass%. By the content of the binder 16 being within this range, the ion conductivity can be improved without decreasing the negative electrode capacity density, and high mechanical strength can be obtained, resulting in more excellent cycle life characteristics. The content of the binder 16 is more preferably 0.5 to 30 mass%. In the present invention, when the negative electrode 1 for a non-aqueous electrolyte secondary battery contains the binder 16, the binder 16 is preferably disposed between the framework forming agent 14 and the second negative electrode active material 17, and between particles of the negative electrode active material 17.
[0055] In the present embodiment, when the conductive assistant and / or binder is included, the content of the skeleton forming agent 14 needs to be calculated taking into consideration the solid content mass of the conductive assistant and the binder. Specifically, when the conductive assistant and / or binder is included, the content of the skeleton forming agent 14 is preferably 3.0 to 40.0 mass% with the total solid content of the negative electrode active material 13, the skeleton forming agent 14, the conductive assistant 15, the binder 16, and the second negative electrode active material 17 being 100 mass%. If the content of the skeleton forming agent 14 is within this range, the above-mentioned effect of using the skeleton forming agent 14 is more reliably exhibited. By making the content of the skeleton forming agent 14 in the negative electrode material 12 3.0 mass% or more, the function of the skeleton forming agent 14 can be more fully obtained. In addition, by making the content of the skeleton forming agent 14 40.0 mass% or less, the decrease in energy density can be more effectively prevented. A more preferable content of the skeleton forming agent 14 is 5.0 to 30.0 mass%.
[0056] [Positive electrode] Next, a positive electrode in the case where the above-mentioned negative electrode is used to construct a lithium ion secondary battery will be described. The positive electrode active material is not particularly limited as long as it is a positive electrode active material that is normally used in lithium ion secondary batteries. For example, positive electrode active materials such as alkali metal transition metal oxides, vanadium, sulfur, solid solutions (lithium excess, sodium excess, potassium excess), carbon, and organic materials can be used.
[0057] The positive electrode for a lithium ion secondary battery of this embodiment may contain a skeletal former, similar to the negative electrode described above. The skeletal former may be the same as that of the negative electrode described above, and the preferred content of the skeletal former is also the same as that of the negative electrode.
[0058] The positive electrode for lithium ion secondary battery of this embodiment may contain a conductive assistant. As the conductive assistant, the above-mentioned various conductive assistants that can be used in the negative electrode are used. The preferred content of the conductive assistant is also the same as that of the negative electrode.
[0059] The positive electrode for lithium ion secondary battery of this embodiment may contain a binder. As the binder, for example, organic materials such as polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), hexafluoropropylene, tetrafluoroethylene, polyacrylic, alginic acid, etc. may be used alone or in combination of two or more. In addition, these organic binders may be mixed with inorganic binders. Examples of inorganic binders include silicate-based, phosphate-based, sol-based, and cement-based binders.
[0060] The current collector used for the positive electrode is not particularly limited as long as it has electronic conductivity and can pass electricity through the positive electrode active material held therein. For example, conductive materials such as C, Ti, Cr, Ni, Cu, Mo, Ru, Rh, Ta, W, Os, Ir, Pt, Au, Al, and alloys containing two or more of these conductive materials (for example, stainless steel and Al-Fe alloy) can be used. When using a conductive material other than the above, for example, a multilayer structure of heterogeneous metals such as iron coated with Al, or heterogeneous elements such as Al coated with C may be used. From the viewpoint of high electrical conductivity and high stability in the electrolyte, C, Ti, Cr, Au, Al, stainless steel, and the like are preferred as the current collector, and further from the viewpoint of oxidation resistance and material cost, C, Al, stainless steel, and the like are preferred. More preferred are carbon-coated Al or Al alloy, and carbon-coated stainless steel.
[0061] The shape of the current collector used in the positive electrode may be linear, rod-like, plate-like, foil-like, or porous, among which the porous shape may be used since it can increase the packing density and the skeleton forming agent can easily penetrate into the active material layer. Examples of the porous shape include mesh, woven fabric, nonwoven fabric, embossed body, punched body, expanded body, and foamed body. The same porous metal body as that of the negative electrode may be used.
[0062] [Separator] In the lithium ion secondary battery of this embodiment, a separator that is generally used in lithium ion secondary batteries can be used, such as a polyethylene microporous film, a polypropylene microporous film, a glass nonwoven fabric, an aramid nonwoven fabric, a polyimide microporous film, or a polyolefin microporous film.
[0063] [Electrolytes] In the lithium ion secondary battery of this embodiment, the electrolyte may be any electrolyte that is commonly used in lithium ion secondary batteries. For example, an electrolyte solution in which an electrolyte is dissolved in a solvent, a gel electrolyte, a solid electrolyte, an ionic liquid, or a molten salt may be used. Here, the electrolyte solution refers to an electrolyte dissolved in a solvent.
[0064] The electrolyte for the lithium ion secondary battery must contain lithium ions as a carrier responsible for electrical conduction, and thus the electrolyte salt is not particularly limited as long as it is used in the lithium ion secondary battery, but a lithium salt is preferable. As the lithium salt, at least one selected from the group consisting of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium trifluoromethanesulfonate (LiCF3SO4), lithium bistrifluoromethanesulfonylimide (LiN(SO2CF3)2), lithium bispentafluoroethanesulfonylimide (LiN(SO2C2F5)2), lithium bisoxalatoborate (LiBC4O8), etc., can be used, or two or more can be used in combination.
[0065] The electrolyte solvent is not particularly limited as long as it is one that is used in lithium ion secondary batteries. For example, at least one selected from the group consisting of propylene carbonate (PC), ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), γ-butyrolactone (GBL), methyl-γ-butyrolactone, dimethoxymethane (DMM), dimethoxyethane (DME), vinylene carbonate (VC), vinylethylene carbonate (EVC), fluoroethylene carbonate (FEC), and ethylene sulfite (ES) can be used, or two or more of them can be used in combination.
[0066] Furthermore, the concentration of the electrolyte (concentration of the salt in the solvent) is not particularly limited, but is preferably 0.1 to 3.0 mol / L, and more preferably 0.8 to 2.0 mol / L.
[0067] Ionic liquids and molten salts are classified into pyridine-based, alicyclic amine-based, aliphatic amine-based, etc., based on the type of cation (positive ion). By selecting the type of anion (negative ion) to be combined with this, a variety of ionic liquids or molten salts can be synthesized. Examples of cations include ammonium-based ions such as imidazolium salts and pyridinium salts, phosphonium-based ions, inorganic ions, etc. Examples of anions include halogen-based ions such as bromide ions and triflates, boron-based ions such as tetraphenylborate, and phosphorus-based ions such as hexafluorophosphate.
[0068] Ionic liquids and molten salts are, for example, cations such as imidazolinium and Br - , Cl - , B.F. 4- , P.F. 6- , (CF3SO2)2N - , CF3SO 3- , FeCl 4- The electrolyte can be obtained by a known synthesis method such as combining with an anion such as the above. If it is an ionic liquid or a molten salt, it can function as an electrolyte without adding an electrolyte.
[0069] Solid electrolytes are classified into sulfide-based, oxide-based, hydride-based, organic polymer-based, etc. Most of these are amorphous or crystalline, consisting of carrier salts and inorganic derivatives. Because there is no need to use flammable aprotic organic solvents like electrolytes, there is less risk of gas or liquid application or liquid leakage, and it is expected to become a secondary battery with excellent safety.
[0070] [Manufacturing method] Next, a method for manufacturing the lithium ion secondary battery according to this embodiment will be described. The method for producing a negative electrode for a lithium ion secondary battery according to the present embodiment includes a first step of forming a negative electrode layer precursor in which a negative electrode material containing a first negative electrode active material is applied to a current collector and dried, and the first negative electrode active material is disposed inside the pores of the current collector made of a porous metal body. For example, a nickel porous material having a thickness of 1000 μm is produced, and a nickel porous body wound in advance in a roll is prepared, while the first negative electrode active material is mixed with N-methyl-2-pyrrolidone or water to prepare a paste-like slurry as a negative electrode material. Next, the inside of the nickel porous body is filled and applied with the slurry-like negative electrode material, dried, and then pressure-adjusted to obtain a negative electrode layer precursor.
[0071] As described above, the negative electrode layer precursor may be left in a wet state without being dried. In addition to the above-mentioned slurry coating, for example, a method of forming a negative electrode active material layer inside a porous current collector and integrating the negative electrode active material (precursor) by using a chemical plating method, a sputtering method, a vapor deposition method, a gas deposition method, a dipping method, a press-in method, a chemical vapor deposition method (CVD), an atomic layer deposition method (ALD), or the like may be used. However, from the viewpoint of the lyophilicity of the framework forming agent and the electrode manufacturing cost, the slurry filling coating method or the dipping method is preferred.
[0072] In the first step, the slurry of the negative electrode material may contain a carbon-based material and / or a conductive assistant. In this case, for example, the first negative electrode active material, the carbon-based material and / or the conductive assistant are mixed with N-methyl-2-pyrrolidone or water to prepare a paste-like slurry, and the negative electrode layer precursor can be obtained through the same procedure as in the first step.
[0073] The method for producing a negative electrode for a lithium ion secondary battery according to the present embodiment also includes a second step of impregnating the negative electrode layer precursor formed in the first step with a skeleton-forming agent containing a silicate having a siloxane bond or a phosphate having a phosphate bond, and drying the skeleton-forming agent to harden the skeleton-forming agent and form a skeleton of the negative electrode active material layer. The second step allows the skeleton-forming agent to be disposed on the first negative electrode active material. For example, a silicate having a siloxane bond or a phosphate having a phosphate bond is purified by a dry or wet method, and then water is added to adjust the mixture to prepare a skeleton-forming agent liquid containing a skeleton-forming agent. At this time, a surfactant may be mixed. As a dry method, for example, an alkali metal silicate can be produced by adding SiO2 to water in which an alkali metal hydroxide is dissolved, and treating the mixture at 150°C to 250°C in an autoclave. As a wet method, for example, a mixture of an alkali metal carbonate compound and SiO2 is fired at 1000°C to 2000°C, and then dissolved in hot water to produce the alkali metal silicate.
[0074] Next, the surface of the negative electrode layer precursor is coated with a skeleton-forming agent liquid to coat the first negative electrode active material. The skeleton-forming agent can be applied by impregnating the negative electrode layer precursor into a tank containing the skeleton-forming agent liquid, or by dripping or applying the skeleton-forming agent onto the surface of the negative electrode layer precursor, spray coating, screen printing, curtain printing, spin coating, gravure coating, die coating, or the like. The skeleton-forming agent applied to the surface of the negative electrode layer precursor penetrates into the inside of the negative electrode and enters into the gaps between the first negative electrode active material and the conductive assistant. Then, the skeleton-forming agent is dried by heat treatment to harden the skeleton-forming agent. As a result, the skeleton-forming agent forms the skeleton of the first negative electrode active material layer.
[0075] The heat treatment is preferably performed at 80°C or higher, more preferably 100°C or higher, and desirably 110°C or higher, because a higher temperature can shorten the heat treatment time and improve the strength of the skeleton-forming agent. The upper limit temperature of the heat treatment is not particularly limited as long as the current collector does not melt, and may be increased to, for example, about 1000°C, which is the melting point of copper. In the case of conventional electrodes, the binder may carbonize or the current collector may soften, so the upper limit temperature was estimated to be much lower than 1000°C. However, in this embodiment, the skeleton-forming agent is used, and the skeleton-forming agent exhibits excellent heat resistance and is stronger than the strength of the current collector, so the upper limit temperature is 1000°C.
[0076] The heat treatment can be performed for a period of 0.5 to 100 hours. The heat treatment may be performed in air, but is preferably performed in a non-oxidizing atmosphere to prevent oxidation of the current collector.
[0077] The method for producing a negative electrode for a lithium ion secondary battery according to the present embodiment also includes a third step of forming a negative electrode layer by applying a negative electrode material containing a second negative electrode active material to the negative electrode layer precursor formed in the second step and drying the applied material. The third step allows the second negative electrode active material to be disposed on the framework forming agent. For example, the negative electrode layer precursor can be obtained by filling and applying the prepared slurry of the negative electrode material containing the second negative electrode active material to the negative electrode layer precursor, drying, and then adjusting the pressure. In addition to the above-mentioned slurry application, the method of introducing the electrode mixture containing the second negative electrode active material includes a method of filling and integrating the second negative electrode active material into the negative electrode layer precursor using a chemical plating method, a sputtering method, a vapor deposition method, a gas deposition method, a dipping method, a press-in method, etc. However, from the viewpoint of electrode manufacturing costs, the slurry filling and application method is preferred.
[0078] In the method for producing a negative electrode for a lithium ion secondary battery according to the present embodiment, the ratio B / A of the density B of the negative electrode layer formed in the fourth step to the density A of the negative electrode layer precursor formed in the first step is 0.9 or less.
[0079] In the method for producing a negative electrode for a lithium ion secondary battery according to the present embodiment, the density A of the negative electrode layer precursor formed in the first step is set to 0.5 to 2.0 g / cm 3 This makes it possible to more reliably set the ratio B / A of the density B of the negative electrode layer to the density A of the negative electrode layer precursor (i.e., density increase ratio) within the above range, thereby enhancing the effect of the above-mentioned framework forming agent. A more preferable range for the density A of the negative electrode layer precursor is 0.6 to 1.5 g / cm 3 The density A of the negative electrode layer precursor is 0.6 g / cm 3 By setting the electrode density at 1.5 g / cm or more, it is possible to suppress the decrease in energy density due to the decrease in electrode density. 3 The capacity reduction can be suppressed by setting the following.
[0080] Furthermore, the method for producing a negative electrode for a lithium ion secondary battery according to this embodiment may include a step between the second step and the third step of forming a conductive path in the negative electrode layer precursor by impregnating the negative electrode layer precursor formed in the second step with a conductive agent solution containing a conductive assistant and / or a binder and drying the solution. This step allows the conductive assistant and / or the binder to be disposed between the framework forming agent and the second negative electrode active material inside the negative electrode layer precursor. For example, a conductive agent solution is prepared by dissolving or dispersing a conductive assistant and / or a binder in N-methyl-2-pyrrolidone or water, and then the conductive agent solution is applied to the surface of the negative electrode layer precursor to coat the negative electrode layer precursor with the conductive agent solution. The conductive material solution containing the conductive assistant and / or binder can be applied by impregnating the negative electrode layer precursor in a tank storing the conductive agent solution, or by dropping or applying the skeleton-forming agent onto the surface of the negative electrode layer precursor, spray coating, screen printing, curtain printing, spin coating, gravure coating, die coating, etc. The conductive assistant and / or binder applied to the surface of the negative electrode layer precursor can dispose the conductive assistant and / or binder between the skeleton-forming agent and the second negative electrode active material, and also permeate into the inside of the negative electrode layer precursor and enter into gaps between the first negative electrode active material, the skeleton-forming agent, etc.
[0081] The positive electrode for lithium ion secondary battery of the present invention has a process for producing a positive electrode by coating a positive electrode material containing a positive electrode active material, a conductive assistant, and a binder on a current collector, drying and rolling the positive electrode material. For example, a rolled aluminum foil having a thickness of 10 μm is produced, and the aluminum foil is prepared in advance in a roll shape, while a positive electrode material is prepared by mixing a positive electrode active material, a binder, a conductive assistant, etc. to prepare a paste-like slurry. Next, the slurry-like positive electrode material is coated on the surface of the aluminum, dried, and then a roll press process is performed to obtain a positive electrode. In addition, a foamed porous body made of metal may be used as the current collector. The current collector is characterized in that the electrode mixture is filled. The method for filling the electrode mixture into the current collector is not particularly limited, but for example, a method of filling the inside of the mesh structure of the current collector with a slurry containing the electrode mixture by applying pressure by a pressing method can be mentioned. After filling the electrode mixture, the filled current collector is dried and then pressed to improve the density of the electrode mixture and adjust it to a desired density.
[0082] Finally, the obtained negative electrode and positive electrode are cut to a desired size, joined together with a separator therebetween, and sealed in an electrolyte to obtain a lithium ion secondary battery. The structure of the lithium ion secondary battery can be applied to existing battery forms and structures such as stacked batteries and wound batteries.
[0083] [effect] According to this embodiment, the following effects are achieved. In this embodiment, the current collector 11 is made of a porous metal body, and a negative electrode material 12 is arranged in the pores of the porous metal body. The negative electrode material 12 is arranged on the inner surface of the pores and includes a first negative electrode active material 13 made of a silicon-based material, a skeleton-forming agent 14 arranged on the first negative electrode active material 13 and containing a silicate having a siloxane bond, and a second negative electrode active material 17 arranged on the skeleton-forming agent.
[0084] First, by using a porous metal body as the current collector 11, it becomes possible to fix the negative electrode material 12 in the micron-sized region by the porous metal skeleton, and peeling and cracking of the negative electrode can be suppressed. Furthermore, by using the framework forming agent 14 as the negative electrode material 12, it becomes possible to fix the negative electrode material 12 in a nano-sized region. More specifically, a third phase is formed by the framework forming agent 14 at the interface between the current collector 11 made of a porous metal body and the negative electrode active material 13 arranged on the inner surface of the pores of the current collector, and the current collector 11 and the negative electrode active material 13 are firmly bound within the current collector pores, thereby preventing them from falling off during expansion and contraction and preventing durability deterioration. Furthermore, by disposing the second negative electrode activator 17 in the voids of the porous metal body in which the first negative electrode active material 13 is bound by the skeletal forming agent 14, i.e., on the skeletal forming agent 14, it can contribute to suppressing the falling off of the negative electrode material 12 that occurs when the first negative electrode active material 13 expands and contracts, thereby suppressing structural deterioration of the electrode and achieving improved energy density and cycle durability. Therefore, by disposing the second negative electrode activator 17 on the framework forming agent 14 that binds the first negative electrode active material 13 inside the pores of the current collector 11, even if the first negative electrode active material 13 made of a silicon-based material having a high capacity and an extremely large expansion and contraction rate is used for the negative electrode, the negative electrode structure can be maintained even when full charge and discharge cycles are performed with an SOC of 0 to 100. Furthermore, it is possible to suppress the falling off and breakage of the conductive path when the capacity is increased by making the negative electrode thicker and the basis weight is high, and it is possible to realize high cycleability and overwhelmingly high energy density.
[0085] In addition to the configuration of this embodiment, when a negative electrode for a nonaqueous electrolyte secondary battery is configured by also including a conductive assistant 15 and / or a binder 16 as shown in FIG. 2, this can contribute to suppressing the falling off of the negative electrode material 12 that occurs during expansion and contraction, and can also contribute to maintaining the electrode structure and reducing the internal resistance. Therefore, deterioration of the electrode structure can be further suppressed, and improvements in energy density and cycle durability can be more effectively achieved. Therefore, by further including the conductive assistant 15 and / or the binder 16 in the configuration of the first embodiment, it is possible to contribute to suppression of the falling off of the negative electrode material 12 that occurs during expansion and contraction, and also to maintenance of the electrode structure and reduction of internal resistance, so that even when a full charge / discharge cycle with an SOC of 0 to 100 is performed, the negative electrode structure can be better maintained, despite the use of the first negative electrode active material 13 made of a silicon-based material with a high capacity and an extremely large expansion and contraction rate. As a result, it is possible to better suppress the falling off and the breakage of the conductive path when the capacity is increased due to the thickening of the negative electrode film or the basis weight is increased, and it is possible to better realize high cycleability and an overwhelmingly high energy density.
[0086] The present invention is not limited to the above embodiment, and modifications and improvements within the scope of the present invention that can achieve the object of the present invention are included in the present invention. For example, a non-aqueous electrolyte secondary battery is a secondary battery (electricity storage device) that uses a non-aqueous electrolyte such as an organic solvent as the electrolyte, and includes sodium ion secondary batteries, potassium ion secondary batteries, magnesium ion secondary batteries, calcium ion secondary batteries, etc. in addition to lithium ion secondary batteries. Also, a lithium ion secondary battery means a secondary battery of a non-aqueous electrolyte that does not contain water as a main component, and a battery in which lithium ions are contained in the carrier responsible for electrical conduction. For example, lithium ion secondary batteries, metal lithium batteries, lithium polymer batteries, all-solid-state lithium batteries, air lithium ion batteries, etc. are included. The same applies to other secondary batteries. Here, a non-aqueous electrolyte that does not contain water as a main component means that the main component in the electrolyte is not water. That is, it is a known electrolyte used in a non-aqueous electrolyte secondary battery. This electrolyte can function as a secondary battery even if it contains some water, but it is desirable that the electrolyte contains as little water as possible because it adversely affects the cycle characteristics, storage characteristics, and input / output characteristics of the secondary battery. In reality, it is preferable that the water in the electrolyte is 5000 ppm or less. EXAMPLES
[0087] Next, examples of the present invention will be described, but the present invention is not limited to these examples.
[0088] <Example 1> [Preparation of negative electrode] A slurry was prepared containing silicon (particle diameter 1 to 3 μm) as a first negative electrode active material and a conductive assistant shown in Table 1. Next, the prepared slurry was filled into a current collector made of "Nickel Celmet" (registered trademark) manufactured by Sumitomo Electric Industries, Ltd., and dried, followed by pressure adjustment treatment to obtain a negative electrode layer precursor.
[0089] On the other hand, a 10 mass% aqueous solution of K2O·3SiO2 was prepared as a skeleton-forming agent solution containing a skeleton-forming agent and water. The negative electrode layer precursor obtained above was immersed in the prepared skeleton-forming agent solution. After immersion, the negative electrode precursor was heated at 160°C and dried.
[0090] A conductive agent solution containing the conductive assistant shown in Table 1 and polyvinylidene fluoride (PVdF) as a binder was prepared. The negative electrode layer precursor obtained above was immersed in the prepared conductive agent solution. After immersion, the negative electrode layer precursor was dried to obtain a negative electrode layer precursor.
[0091] As a second negative electrode active material, a slurry containing the compounds shown in Table 1 was prepared. Next, the prepared slurry was filled into the negative electrode layer precursor obtained above and dried to obtain a negative electrode having a negative electrode layer formed thereon.
[0092] [Preparation of positive electrode] As the positive electrode active material, LiNi 0.5 Co 0.2 Mn 0.3 A positive electrode mixture slurry was prepared by mixing 94% by mass of the positive electrode active material, 4% by mass of carbon black as a conductive assistant, and 2% by mass of polyvinylidene fluoride (PVdF) as a binder, and dispersing the mixture in an appropriate amount of N-methyl-2-pyrrolidone (NMP). A current collector with a thickness of 1.0 mm, porosity of 95%, number of cells of 46 to 50 per inch, pore size of 0.5 mm, and specific surface area of 5000 m was used. 2 / m 3 The prepared positive electrode mixture slurry was applied by the pressure injection method to a coating amount of 90 mg / cm. 2The mixture was dried in a vacuum at 120° C. for 12 hours, and then roll pressed at a pressure of 15 tons to produce a positive electrode for a lithium ion secondary battery in which the pores of the foamed aluminum were filled with the electrode mixture.
[0093] [Preparation of lithium-ion secondary batteries] A microporous membrane having a thickness of 25 μm and a three-layer laminate of polypropylene / polyethylene / polypropylene was prepared as a separator, and punched out to a size of 100 mm length × 90 mm width. The positive electrode for lithium ion secondary battery and the negative electrode for lithium ion secondary battery obtained above were stacked in the order of positive electrode / separator / negative electrode / separator / positive electrode / negative electrode to produce an electrode laminate.
[0094] Then, a tab lead was ultrasonically welded to the current collecting area of each electrode. The electrode laminate with the welded tab lead was inserted into a bag-shaped aluminum laminate for secondary batteries that was heat sealed to produce a laminate cell. As an electrolyte, a solution was prepared by dissolving 1.2 moles of LiPF6 in a solvent that was a mixture of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a volume ratio of 3:4:3, and this solution was injected into the laminate cell to produce a lithium ion secondary battery.
[0095] <Examples 2 to 4> As a second negative electrode active material, a slurry containing the negative electrode active material shown in Table 1 was prepared. Next, the prepared slurry was filled into the negative electrode layer precursor in the same manner as in Example 1, and dried to form a negative electrode layer, thereby obtaining the negative electrodes of Examples 2 to 4.
[0096] In addition, the positive electrodes of Examples 2 to 4 have the same coating amount as in Example 1 of 45 mg / cm 2 Except for the above change, the battery was fabricated in the same manner as in Example 1. The battery was fabricated in the same manner as in Example 1.
[0097] <Comparative Example 1> The negative electrode was produced in the same manner as in Examples 1 to 4, except that the second negative electrode active material was not used in producing the negative electrode.
[0098] The positive electrode of Comparative Example 1 had a coating amount of 45 mg / cm2 2 Except for the above change, the battery was fabricated in the same manner as in Example 1. The battery was fabricated in the same manner as in Example 1.
[0099] [Aging test] An aging test was carried out on each of the Examples and Comparative Examples. The aging test was carried out at a test environment temperature of 25°C.
[0100] [Durability test] A cycle life test was carried out for each of the Examples and Comparative Examples. The cycle life test was carried out at a test environment temperature of 25° C., a current density of 0.2 C-rate, and a cutoff potential of 2.5 to 4.2 V.
[0101] [Table 1]
[0102] Fig. 3 is a diagram showing the relationship between the number of cycles and the active material capacity (mAh / g) in Examples 1 to 4 and Comparative Example 1. As is clear from Fig. 3, according to this example, the amount of decrease in the active material capacity is small even when the number of cycles increases, and therefore it was confirmed that it is possible to obtain a negative electrode for a nonaqueous electrolyte secondary battery and a nonaqueous electrolyte secondary battery including the same that can suppress deterioration in durability and deterioration of the electrode structure and improve the energy density and cycle durability. [Explanation of symbols]
[0103] 1 Negative electrode for nonaqueous electrolyte secondary batteries 11 Current collector 12 Anode materials 13 First negative electrode active material (negative electrode active material composed of silicon-based material) 14 Skeleton-forming agents 15 Conductive additives 16 Binder 17 Second negative electrode active material
Claims
1. A current collector made of a porous metal body; a negative electrode material disposed in the pores of the porous metal body; The negative electrode material is a first negative electrode active material disposed on an inner surface of the pore and composed of a silicon-based material; a framework forming agent disposed on the first negative electrode active material and including a silicate having a siloxane bond; a second negative electrode active material disposed on the framework forming agent.
2. 2. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the negative electrode material further comprises a conductive assistant disposed between the framework forming agent and the second negative electrode active material.
3. The negative electrode for a non-aqueous electrolyte secondary battery in accordance with claim 1 , wherein the negative electrode material further comprises a binder.
4. 3. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the framework forming agent comprises a silicate represented by the following general formula (1): [Chemical formula 1] A 2 O·nSiO 2 ... Formula (1) [In the above general formula (1), A represents an alkali metal, and n is 1.6 or more and 3.9 or less.]
5. 4. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the porous metal body is a foamed metal body.
6. A non-aqueous electrolyte secondary battery comprising the negative electrode for a non-aqueous electrolyte secondary battery according to claim 1 .
Citation Information
Patent Citations
Control method of idle speed
JP1986049147A
Resin composition
JP1988069818A
Nonaqueous electrolyte secondary battery
JP2004259636A
Skeleton forming agent and negative electrode using the same
JP2018085276A
Flexible electrode, method of manufacturing the same, and secondary battery including the same
JP2019537233A